Sonochemical synthesis of nanodispersed molybdenum, tun gsten, and vanadium oxides - Logvinovich, Alexander S.; Sviridova, Tatyana V.; Sadovskaya, Lyubov Yu.; Sviridov, Dmitry V. (Journal of the Belarusian State University. Chemistry, 2019)
It is shown that the effect of ultrasound on the aqueous solutions of molybdic, tungstic and vanadic oxoacids results in the catalytic enhancement of their polycondensation only in the presence of the surface of redoxactive metal (nickel, cobalt) in the ultrasonic field. It is revealed that the involvement of redox centers at the metal surface in the sonoinduced olation makes the formation of oxide phase to be a directional one leading to the synthesis of needlelike oxide particles.
Keywords: ultrasound; molybdenum oxide; vanadium oxide; tungsten oxide; oxoacids; polycondensation